Do Not Be Fooled by Fancy Mutations: Inflammatory Fibroid Polyps Can Harbor Mutations Similar to Those Found in GIST - Bodil Bjerkehagen; Kristin Aaberg; Sonja E. Steigen (Case Reports in Medicine)
Goal. Surgeons that remove a typical polyp from the stomach or small intestine should be reluctant to accept a diagnosis of GIST just because there is a mutation in platelet-derived growth factor receptor alfa (PDGFRA). Background. A subtype of gastric and intestinal polyps is denoted as inflammatory fibroid polyp (IFP). In some of these cases a mutation in PDGFRA is found, leading to the diagnosis of gastrointestinal stromal tumor (GIST). Study. This study includes two patients that had polyps removed from the ileum, and an extended investigation was performed with immunohistochemical staining and mutation analyses. Results. The tumors did not show typical immunohistochemical staining for markers used to diagnose GIST, but the mutation analysis revealed a mutation in PDGFRA exon 12. On the basis of the mutation analysis, both polyps were primarily diagnosed as GISTs, but the diagnosis was later changed to inflammatory fibroid polyp. Conclusion. It is important that both surgeons and pathologists be aware that IFP can harbor a mutation in PDGFRA where further treatment and follow-up is different with the two different diagnoses. A mutation analysis can be misleading when taken out of the context of clinical observations, histological characteristics and immunohistochemical staining.